Regards croisés sur les transferts culturels gréco-roumains : bilan d’un siècle (xxe siècle) - Anna Tabaki (Cahiers Balkaniques)
In this approach I will attempt to sketch, using the work of a vast range of Greek and Romanian intellectuals, the reciprocal interests, thematic resemblances as well as a few important research directions pursued by both sides throughout the 20th century concerning diachronic and synchronic Greco-Romanian cultural transfers. There are many converging attitudes regarding the study of the Byzantine and post-Byzantine tradition (on the ideological front as well as the literary one), the way the Enlightenment ideas were received and the formation of the modern way of thinking, literary comparatism, the education system and the place of the Greek language, the ideological changes in historiography in the 20th century (history of ideas, history of mentalities, socio-economic history). Granted, a few major and versatile phenomena remain at the epicentre of it all, such as Phanariotism and the Greek diaspora in Romania.